Evaluation Of The Intersection Across Personality And Online Behavior - Azam, Shamshul (Digital Repository of Theses - SSBM Geneva, 2025)
This research is being conducted to identify the Intersection across personality and online behavior also to understand how people are using internet in their daily life. The central question posed is: To understanding the personality and online behavior with the evolution of internet. The goal is to analyze data from interviews conducted with any internet user and create a theoretical framework for health practitioners, marketing manager, environmentalist, and individuals. The study used a quantitative research & qualitative research design by conducting semi-structured interviews over Zoom, Google Chat, email, survey form and face to face based on the life experience of the interviewees. Observation techniques and the interviewees responses were gathered to generate data from a target population Note: Generation names are based on when members of that generation become adults (18-21), Brunjes (2024, p. 1) Interviewees population is mixed and involve all the valid age group who have access to internet and use it. An abductive approach was applied to the study, and themes were formed after the data from the interviews was analyzed. The findings showed that the 3rd driving factor to visit internet services is social media primarily. The findings of this study may be used by health Practitioners, marketing manager, environmentalist